Increasing the Comfort of Hypertension Sufferers Through Effleurage Back Massage - Widayati, Dhina; Rachmania, Diana; Safitri, Nabila (Chakra Brahmanda Lentera Institute, 2024)
Background: Comfort is one of the basic needs that is holistic. Hypertension sufferers often feel discomfort due to increased blood pressure, so these basic needs are not appropriately met. Effleurage back massage intervention is one method used to overcome discomfort in hypertension sufferers. The aim of this research was to determine the effect of efflurage back massage on the comfort level of hypertension sufferers Methods: The research design used pre-experiment, involving 32 respondents through purposive sampling from a population of 42 people with hypertension. The comfort variable was measured using the SGCQ questionnaire sheet and the results were analyzed using the Independent T-Test with α 0.05 Results: The research results showed an increase in comfort from almost all (75%) respondents in the very uncomfortable category in the pretest results to almost all (93.7%) respondents in the very comfortable category in the post test. The Wilcoxon results obtained p-value = 0.001 (<α), indicating that effleurage back massage intervention can increase comfort in hypertension sufferers. Conclusion: Giving effleurage back massage can trigger endorphin neurotransmitters in the autonomic nerves which make blood circulation smooth so that the body relaxes. This intervention can be applied as a non-pharmacological therapy in the management of hypertension.